Modification of Topsoil Physico-Chemical Characteristics and Macroinvertebrates Structure Consecutive to the Conversion of Secondary Forests into Rubber Plantations in Grand-Lahou, Côte d’Ivoire (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
The objective of this investigation was to assess the modifications of topsoil physico-chemical characteristics and macroinvertebrates structure consecutive to the conversion of secondary forests into rubber plantations and how these change with the aging of the plantations and the season. The sampling design was constituted of four treatments: secondary forest referred to as baseline land use, 7-, 12- and 25 year old rubber plantations. Three replications per land use type were randomly established in each of the selected treatments, thus totaling 12 sampling areas. On each sampling area, a 40 m transect was established. The litter dwelling and topsoil (0-10 cm) macroinvertebrates were sampled, respectively, by using the pitfall traps and monoliths (50 cm × 50 cm × 10 cm) following the Tropical Soil Biology and Fertility method. The soil physical and chemical parameters were measured along the 40 m transect. The results showed that the conversion of secondary forest into plantations was characterized by a modification of the density of soil macroinvertebrates (dry season: -50 and -24% vs. rainy season: -61 and +32%), taxonomic richness of soil macroinvertebrates (dry season: +7 and -14% vs. rainy season: -21 and -14%), water content (dry season: -41 and -5% vs. rainy season: -62 and -31%), bulk density (dry season: +6 and -3% vs. rainy season: +33 and +29%), soil organic carbon (dry season: -73 and -59% vs. rainy season: -67 and -51%) and total nitrogen (dry season: -68 and -58% vs. rainy season: -64 and -52%), respectively, after about 7 and 25 years of conversion. The restoration processes did not cause significant changes in the soil physico-chemical and biological characteristics after 25 years of forests conversion. However, the study highlighted the improvement in the soil ecological quality due to a reduction in soil degradation, and an increase in the density of macroinvertebrates (+235%), taxono mic richness (+9%), water content (+84%), soil organic carbon (+50%) and total nitrogen (+33%) in the 25 year old plantations compared to the 7 year old plantations.